Free radical scavenging properties and induction of apoptotic effects of FA fraction obtained after proteolysis of bioactive peptides from microalgae Synechococcus sp. VDW - Suttisuwan, Rutairat (Array, 2019)
This study aims to determine the antioxidant activity of bioactive peptides derived from Synechococcus sp. VDW cells cultured for 21 days. Synechococcus sp. VDW protein hydrolysates were prepared with trypsin and purified by ultrafiltration with molecular mass cut-off membranes of 10, 5 and 3 kDa.